Perfection of physical training of students and listeners of educational establishments of Ministry of Internal Affairs of Russia - N.A. Alekseev; N.B. Kutergin; A.N. Kulinichev (Physical Education of Students, 2013)
Directions of perfection of students' physical training and listeners of educational establishments of Ministry of Internal Affairs of Russia are considered. These statistical Ministries are resulted on crimes. It is marked that criminals perfect the actions constantly, apply the new methods of commission of crime, all more frequent utillize different armaments and explosive devices. The necessity of increase of professionalism and capacity of students is marked. The comparative analysis of normative acts of Ministry is resulted. The elements of alertness of employees are selected to implementation operatively-official tasks. Technical descriptions of equipment which is utillized by employees at implementation of the special operations are considered. The chart of distributing of clock is offered in the section of the program on a body-conditioning. It is suggested to extend the section of general and special endurance, utillize the methods of preparation of weightlifters. Directions of increase military efficiency of organs of internal affairs are shown through perfection of physical qualities: force, endurance, quickness, adroitness.